ANEMIA PREVENTION EFFORTS THROUGH HEALTH EDUCATION FOR ADOLESCENT GIRLS: - - S.Kep.Ns., M.Kes, Riesmiyatiningdyah,; Afandi, Khoirul; Diana Putri, Sherly; Sofia, Ananda (Community Service Journal of Indonesia, 2025)
Prevention and treatment of anemia in adolescent girls must be carried out through a comprehensive approach. Health education about anemia in adolescent girls must be accompanied by special education for adolescent girls about the importance of an active lifestyle and a healthy diet. The results of community service activities regarding anemia prevention efforts through health education for adolescent girls show that the number of counseling participants who have a good level of knowledge before the implementation of the counseling activity about anemia is 5 people to 15 participants. The level of knowledge is poor before the implementation of the counseling activity is 7 people to no participants who have a low level of knowledge. The number of participants with a good level of knowledge about iron supplements before the counseling activity is 4 participants and after the counseling activity the number of participants with a good level of knowledge is 14 people. The number of participants with a low level of knowledge before the counseling activity is 9 people and after the counseling activity there are no participants who have a low level of knowledge. The results of the Hb check show that none of the participants suffer from anemia, the average Hb level obtained is normal at 12 mg / dl. Overall, this activity has a positive impact in increasing awareness among young women in increasing their knowledge about anemia and iron tablets